Embryotoxicity and Physiological Compensation in Chicken Embryos Exposed to Crude Oil - do Amaral-Silva, Lara [UNESP]; Rojas-Antich, Maria Carolina; Dubansky, Benjamin; Tazawa, Hiroshi; Burggren, Warren W. (Oxford University Press (OUP), 2021)
Terrestrial, marine, or aquatic oil spills can directly or indirectly contaminate bird eggs. We hypothesized that chicken embryos exposed to crude oil can physiologically compensate to mitigate the potentially toxic effect of lower doses of oil. Embryos exposed to 0, 1, 3, or 5 µL of oil on embryonic days 4 and 10 were initially analyzed for mortality. All oil doses decreased day 4 embryo survival, but only the 2 highest oil doses lowered survival when applied on day 10. Thus, day 15 embryos treated with 1, 3, and 5 µL of source oil on day 10 had arterialized blood analyzed. The hematological variables hematocrit, red blood cell concentration ([RBC]), and hemoglobin concentration increased in response to 1 µL, were unchanged by 3 µL, and decreased by 5 µL of oil treatment. No changes occurred in arterialized blood gas variables (partial pressure of O2 [PO2], pH, bicarbonate concentration) for 1 and 3 µL embryos, but 5 µL of oil decreased PO2 and caused metabolic acidosis. Increased blood lactate in embryos treated with 3 and 5 µL of oil was correlated with decreased hematocrit and [RBC] and increased body mass, the latter likely reflecting edema. We conclude that embryos in middle development physiologically compensated for negative effects of lower doses of crude oil but that higher doses of oil were harmful to the embryos at all developmental stages. Environ Toxicol Chem 2021;40:2347–2358. © 2021 SETAC.
Keywords: Avian toxicity; Blood variables; Embryotoxicity; Oil spills; Physiological regulation; Stressors; Toxic effects